Bohumil Hrabal and Umberto Eco: Ad Usum Delphini? - Soliński, Wojciech (2023)
This short article came about as a result of the surprising observation that two writers who differ in their backgrounds, education, professional activities, and who are generally associated with works aimed at an adult readership, at some point directed several works to a children's audience. This episodic activity of an academic lecturer and prose writer creating himself as a poet of the outcast resulted in narrative works with characteristics of fairy tales. Three "professorial" fairy tales by U. Eco are described here as modern philosophical poems on the side effects of human civilization. Two animal fables by B. Hrabal (animals speak with a human voice in them) are a bitter reverie on the attitude of humans to animals, on the situation of farmed animals (meat, skins, etc.) and the questionable future of hunting. The article closes with a list of "animal" works by the Czech writer.
Keywords: fairy tale; animal fable; philosophical tale; animal studies; animal world and the civilizing mission of mankind